Bismarck's Institutions A Historical Perspective on the Social Security Hypothesis - Scheubel, Beatrice (Mohr Siebeck, 2013)
The decline in birth rates in advanced economies is not a new phenomenon. Between 1880 and 1900 birth rates dropped from 5.5 children per woman to 2.5 children per woman. A further decline from 2.5 to 1.5 or even 1.3 children took much longer - about 80 years. One of the most apparent causes is, however, widely ignored. Beatrice Scheubel tries to fill this gap. According to the so-called Social Security Hypothesis, insurance against the risks of life (i.e. poverty for all sorts of reasons, in particular, age) by the state crowds out all types of private insurance. One of the (vast) different possibilities to privately insure oneself against poverty is having children. That is why it should not be surprising to witness falling birth rates given the sheer magnitude of the welfare state. In this book, Beatrice Scheubel analyses the effects of the first comprehensive system of social security, which was introduced between 1883 and 1891 in Germany.